Suicide Terrorism: Menelusuri Justifikasi Fikih dalam Literatur Jihad Kontemporer - Rusli Rusli (AL-TAHRIR, 2013)
Abstract: This paper deals with the issue of suicide terrorism or suicidal bombing which has been used as a serious tactic by terrorist organizations or radical and puritan religious movements. The motive behind this kind of action varies greatly, ranging from religious, cultural, political, to social issues. In the literatures on jiha>d, there are various points of view regarding the legality and validity of suicidal attack. First, those who allow this act and regard it as a part of the tactic and strategy of jiha>d, such as radical islamist movements (Salafi-jiha>dists). Second, those who allow it on several conditions, such as Salafi-intellectual (salafiyyah ‘ilmiyyah) and Salafi-reformists (salafiyyah is}la>hiyyah). Third, those who prohibit this act absolutely, such as Salafi-wahha>bists (salafiyyah wahha>biyyah), who based their arguments on the assumption that this is regarded as the act that is prohibited in Islam, and there is no legal precedence in the history of Islamic law that allows the attack to civil people (women, children, and old men) and non-military targets.